Acute Renal Failure in Neonates and Practice of Acute Peritoneal Dialysis - Tabel, Yilmaz; Suna Celiloglu, Ozgu; Mungan Akin, Ilke; Yakinci, Cengiz (Annals of Medical Research, 2021)
None
Keywords: Acute renal failure, Continue renal replacement treatment, Dialysis, Peritoneal dialysis, Newborn